THE IMPLEMENTATION OF MUNICIPAL WASTE MANAGEMENT POLICY IN BANDUNG CITY - Kurniadi, Budi; Nuryani, Elin (Journal of Indonesian Rural and Regional Government, 2023)
This research is motivated by the increasing production of waste in Bandung City but is not balanced with optimal waste management, based on the background of the research, the researcher identified the problem, namely: How is the implementation of waste management policies in Bandung City. The researcher's goal is to find out and analyze in depth the implementation of waste management policies in Bandung City. The theory used in this study is the Policy Implementation Theory put forward by Charle O. Jones which includes Organization, Interpretation, and Application. Based on the theoretical approach, the researcher formulated the proposition that the implementation of waste management policies in Bandung City will run optimally if the Organization, Interpretation and Application factors are implemented. The method used in this study is the Qualitative Method with a descriptive approach. The data collection techniques in this study were through Observation, Interviews and Documentation. Based on the results of the study, it can be concluded that the Implementation of Waste Management Policies in Bandung City based on Bandung City Regional Regulation number 9 of 2018 concerning waste management has not run optimally, there are still inhibiting factors including lack of external facilities and infrastructure, lack of coordination with various parties, lack of socialization, and lack of assertiveness in enforcing regulations. Efforts that must be made by the Bandung City and Regional Environmental and Sanitation Service are by improving facilities and infrastructure in the region, improving coordination with various parties, conducting routine socialization with the community directly, and increasing firmness in enforcing regulations.